Nutritional Evaluation of Quinoa Genetic Resources Growing in the Climatic Conditions of Central Europe - Dostalíková, Lucie; Hlásná Čepková, Petra; Janovská, Dagmar; Svoboda, Pavel; Jágr, Michal; Dvořáček, Václav; Viehmannová, Iva (Foods (Basel, Switzerland), 2023)
Quinoa displays huge genetic variability and adaptability to distinct climatic conditions. Quinoa seeds are a good source of nutrients; however, the overall nutritional composition and nutrient content is influenced by numerous factors. This study focused on the nutritional and morphologic evaluation of various quinoa genotypes grown in the Czech Republic. Significant differences between years were observed for morphological traits (plant height, inflorescence length, weight of thousand seeds). The weather conditions in the year 2018 were favorable for all the morphological traits. The protein content of quinoa accessions ranged between 13.44 and 20.01% and it was positively correlated to mauritianin. Total phenolic content varied greatly from year to year, while the antioxidant activity remained relatively stable. The most abundant phenolic compounds were the flavonoids miquelianin, rutin, and isoquercetin. Isoquercetin, quercetin, and N-feruoloyl octopamine showed the highest stability under variable weather conditions in the analyzed years. A total of six compounds were detected and quantified in quinoa for the first time. Most varieties performed well under Central European conditions and can be considered a good source of nutrients and bioactive compounds. These data can be used as a source of information for plant breeders aiming to improve the quality traits of quinoa.
Keywords: protein; mass spectrometry; Chenopodium; phenolic compounds; breeding; quinoa